2012
DOI: 10.1002/chem.201203072
|View full text |Cite
|
Sign up to set email alerts
|

New Vistas in N‐Heterocyclic Silylene (NHSi) Transition‐Metal Coordination Chemistry: Syntheses, Structures and Reactivity towards Activation of Small Molecules

Abstract: This account is a review on the synthesis and transition-metal coordination chemistry of N-heterocyclic silylenes (NHSi's) over the last 20 years till the present time (2012). Recently, fascinating and novel synthetic methods have been developed to access transition-metal-NHSi complexes as an emerging class of compounds with a wealth of intriguing reactivity patterns. The striking influence of coordinating NHSi's to transition-metal complex fragments affording different reactivities to the "free" NHSi is a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 271 publications
(120 citation statements)
references
References 109 publications
1
114
0
4
Order By: Relevance
“…The related Si(I) dimer (12) (for an excellent, detailed and up-to-date review on the reactivity of interconnected bis-silylenes such as 12, see [33]) can also activate We have recently (2012) comprehensively reviewed all NHSi transition metal complexes, where we showed that a large array of NHSi complexes from group 4 to group 10 now exist [38,39]. In this section we will limit the discussion to recent and representative examples of NHSi complexes that have been implicated in catalytic transformations, or interesting small molecule activation reactions over the last few years.…”
Section: Free N-heterocyclic Silylenes (Nhsis) and Their Reactivity Tmentioning
confidence: 98%
“…The related Si(I) dimer (12) (for an excellent, detailed and up-to-date review on the reactivity of interconnected bis-silylenes such as 12, see [33]) can also activate We have recently (2012) comprehensively reviewed all NHSi transition metal complexes, where we showed that a large array of NHSi complexes from group 4 to group 10 now exist [38,39]. In this section we will limit the discussion to recent and representative examples of NHSi complexes that have been implicated in catalytic transformations, or interesting small molecule activation reactions over the last few years.…”
Section: Free N-heterocyclic Silylenes (Nhsis) and Their Reactivity Tmentioning
confidence: 98%
“…4 σ-Stabilized metallylene (silylene or germylene) donor ligands also have given rise to unique properties and reactivities. 5,6 It is noteworthy that bis-silylene and -germylene pincer moieties are more σ-donating than P III -based ligands.…”
Section: And [Pcp]mentioning
confidence: 99%
“…Obviously, the heavier analogues possess distinct electronic features compared to the NHCs, and hence exhibit different reactivities [3,4]. While N-heterocyclic silylenes (NHSi) have been engaged as ancillary ligands in numerous homogeneous catalysis [5][6][7], N-heterocyclic germylenes (NHGe) serve as a precursor for polymerization chemistry [8][9][10] and also for chemical vapour depositions [11].…”
Section: Introductionmentioning
confidence: 99%